Efektivitas Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) dalam Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas IV - Yuliyanah, Eva; Andri Valen; Dea Widaswari (JOEAI (Journal of Education and Instruction), 2025)
This study aims to develop animated video learning media on the topic “Indonesiaku Kaya Budaya” for fourth-grade students at SDN Wukirsari. The research method employed was Research and Development (R&D) using the adapted ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were fourth-grade students of SDN Wukirsari. Based on the analysis conducted by three experts—language expert, media expert, and material expert—it was found that the animated video learning media met the “High” validity category with an average score of 0.85. Furthermore, the analysis of student and teacher assessment sheets indicated that the media was categorized as “very practical” with an average score of 82.95. The effectiveness analysis, based on pre-test and post-test results, showed an improvement with an average N-Gain score of 0.73, which falls into the high category. In conclusion, the animated video learning media on “Indonesiaku Kaya Budaya” is valid, practical, and effective, and thus can be used in the learning process.   Keywords: animated video, elementary school, social studies